LITERASI PANCASILA KAUM SARUNGAN DALAM MEWUJUDKAN CIVIL SOCIETY - MAHMUD, MAHMUD (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2023)
Pancasila literacy is a critical understanding of the Indonesian nation based on Pancasila values which are reflected in various forms of mindsets, perspectives, and behaviors. The development of an Indonesian society is based on the spirit of the essence of Pancasila values as a common ideal in order to realize a prosperous, harmonious, mutually respectful (tolerance), just, and peaceful life order. The role of the sarungan through the journey of educational rituals in Islamic boarding schools in the process of transforming nation building is reflected in filling the pages of the nation's history, both political, economic, educational and socio-cultural aspects. The purpose of this paper study is expected to provide an understanding of the Pancasila literacy of the sarungan in realizing civil society. This study uses library research in collecting research data which is then analyzed using technical content analysis. The results of the study illustrate that the ability of the sarungan in realizing civil society is obtained through educational rituals in pesantren to produce sarungan people with charity, and does not rule out the cultivation of national values, namely the values of Pancasila. ABSTRAKLiterasi Pancasila merupakan pemahaman kritis bangsa Indonesia berlandaskan nilai-nilai Pancasila yang tercermin dalam berbagai bentuk pola pikir, perspektif, dan perilaku. Pembangunan masyarakat berkeindonesiaan berlandaskan semangat intisari nilai-nilai Pancasila sebagai cita-cita bersama demi mewujudkan sebuah tatanan kehidupan yang sejahtera, rukun, saling menghargai (toleransi), adil, dan damai. Peran kaum sarungan melalui perjalanan ritual pendidikan di pondok pesantren dalam proses transformasi pembangunan bangsa tercermin dalam mengisi lembaran sejarah bangsa, baik aspek politik, ekonomi, pendidikan maupun sosial budaya. Tujuan kajian tulisan ini diharapkan dapat memberikan pemahaman tentang literasi Pancasila kaum sarungan dalam mewujudkan civil society. Kajian ini menggunakan método riset kepustakaan (library research) dalam menghimpun data-data penelitian yang kemudian dianalisis menggunakan teknis analisis konten. Hasil telaah menggambarkan bahwa kemampuan kaum sarungan dalam mewujudkan civil society diperoleh melalui ritual pendidikan di pesantren untuk mencetak kaum sarungan yang berakhlakul karimah, dan tidak mengesampingkan penanaman nilai-nilai kebangsaan yakni nilai-nilai Pancasila.